INFLUENCE OF CONTINUOUS MONITORING OF THERMAL ENERGY INDICATORS OF REFRIGERATION ENGINEERING ON THE QUALITY OF FOOD STORAGE (Spectrum Journal of Innovation, Reforms and Development, 2022)
The article provides information about the importance of stable value of thermal operation modes of refrigeration engineering under conditions of changing heat load on the compressor. At the same time the task of minimum power consumption by a refrigeration machine is considered. These two parameters characterize the quality of food storage in refrigeration machines. It is shown that temperature stability in cooling chambers and minimum energy consumption for the cooling process determine the efficiency of a refrigeration machine and, ultimately, determine the cost of products. The article describes an approach to achieving this goal, which consists in continuous monitoring of heat and power indicators of the refrigeration machine.